Polscy aktorzy a międzywojenne kino jidysz - MAZUR, DARIA (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
Polish actors and Yiddish cinema of the inter-war period The author presents the thesis that despite the cloistered character of the interwar era Yiddish cinema, Polish actors left their mark on Yiddish productions. Their participation in two silent films, which didn’t survive the war - Jeden z 36 and W lasach polskich were connected to the topic of assimilation, the community of faith and the historical experience of fighting with the invaders, as well as the main idea of rapprochement between the two nations. Polish actors’ roles were connected to non-Jewish characters, although one very important exception to this rule was the role of Berek Joselewicz. The Yiddish cinema of the late-1930’s, which was dominated by escapist stories detached from the contemporary social-political reality, does not contain any trace of cooperation with Polish actors. As the public press from the interwar era as well as from the years after the Second World War shows, its subject-matter was, however, rendered taboo by some Polish participants of interwar-period Jewish film productions, even though the initiative for creating the films ostensibily to break down prejudices and stereotypes was in, in fact, Polish.